Etiological structure of anemia in HIV-infected children - T. A. Daminov; L. N. Tuychiev; G. K. Khudaykulova; Sh. B. Rakhmatullaeva (Детские инфекции (Москва), 2019)
In most cases, HIV infection in children is accompanied by the development of anemia with a decrease in hemoglobin  levels.We studied the structure of anemia in 114 children  with HIV infection aged from 1 year to 18 years. Depending on the clinical stage of HIV infection, the patients were divided into 3 groups: 1st group — 20 children with the second clinical stage of HIV infection;  2nd group — 74 children with the third clinical stage; 3rd group — 20 children with a fourth clinical stage. Serum iron and ferritin were determined.In the majority of patients (95.2%) of the studied groups iron deficiency anemia (IDA) was detected, in 4.8% of cases anemia of chronic diseases (ACD) was detected.The importance of differentiation of the identified anemia determines the therapeutic tactics and the need for the appointment of iron-containing drugs.